Peluang dan Tantangan Formulasi Metode Studi Islam - Asmawi, Asmawi (ISLAMICA: Jurnal Studi Keislaman, 2010)
In speaking of Islamic studies, we need to remember two things. First is the approach by which we elaborate certain point from certain perspective. In Islamic studiesâlike in any other studiesâapproaches vary. Different approaches would bring different conclusions. However, as long as an approach is academically sound and acceptable and meets all standards required, any conclusion resulted thereon is deemed correct and justifiable. Hence, no single conclusion is considered right while the other is wrong. Islamic studies should therefore acknowledge that academic truth is not singular but plural on the ground that there are many approaches toward many conclusions. It is this notion that we want to discuss here. We are interested in exploring the notion of intellectual truth. We hold that differences in opinion should be accepted as natural. Second is, that there is no fundamental differences in the basic value of sciences of any kinds. In other words, what is popularly known as Western science and Islamic science does not in principle differ. Science is science. There cannot be a dichotomy between Islamic or non-Islamic science. Dichotomy in science is not acceptable. Science belongs to all culture, tradition and religion. It does not know particularity. It is universal. Islamic studies should understand this, and use all tools, approaches, methodologiesâalbeit Westernâfor their improvement. It is toward these issues that this paper is destined.